50 Jahre Sektion Erwachsenenbildung in der Deutschen Gesellschaft für Erziehungswissenschaft Konstituierendes - Errungenes - Umbrüchiges aus einem halben Jahrhundert Sektionsgeschichte - Grotlüschen, Anke; Käpplinger, Bernd; Molzberger, Gabriele (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2022)
The section and educational sub-discipline of adult education looks back on 50 years of history. The authors supplement the already drawn interim balance on the 40th anniversary of the founding in 2011/2012 with new studies with additional perspectives. One thematic focus is on memory histories of collective self-assurance and analyses of discipline- and section-historical signposts. The volume contributes to the promotion of a discplinary memory and opens it up to questions related to the present.